Analisis Tingkat Pengetahuan Taktik dan Strategi Futsal pada Pemain Ekstrakurikuler SMAN 2 Kerinci - Tuqya, Habil; Munar, Hendri; Yanto, Anggel Hardi (MAN Insan Cendekia Jambi, 2025)
This research was conducted to identify the extent of understanding of futsal strategies and tactics among students participating in futsal extracurricular activities at SMAN 2 Kerinci. The approach used was a quantitative descriptive method through a questionnaire instrument containing 47 statement items. The study population included all 20 members of futsal extracurricular at SMAN 2 Kerinci with the application of total sampling technique. Data processing was carried out using descriptive statistics and percentage analysis. Findings indicate that understanding of futsal strategies and tactics among SMAN 2 Kerinci extracurricular students falls into the adequate category with an average score of 26. The distribution of results shows no students (0%) in the very weak category, 45% in the weak category, 5% in the adequate category, 50% in the good category, and none (0%) in the very good category.